Murder by accident - Enders, Jody (University of Chicago Press, 2009)
In this work, the author boldly resurrects the long-disgraced concept of intentionality, especially as it relates to the theatre. She contends that the marginalization of intention in critical discourse is a mirror for the marginalization of theatre.
10.7208/chicago/9780226207858.001.0001/upso-9780226207834
Keywords: Theater; Drama; Mord; Gewalt; Drama; Medieval; Violence in the theater; Intention in literature